Two protocols using fluralaner for Rhipicephalus microplus strategic control on taurine cattle in a tropical region - Lidia Mendes de Aquino; Dina Maria Beltran Zapa; Daniel de Castro Rodrigues; Tom Strydom; Siddhartha Torres; Lorena Lopes Ferreira; Francisco Barufi; Heitor Oliveira Arriero de Amaral; Fernando de Almeida de Borges; Tiago Gallina; Rafael Paranhos de Mendonça; Vando Edésio Soares; et al. (Parasites & Vectors, 2024)
Abstract Background The present study aimed to evaluate the effects of different treatment strategies using a new commercial formulation containing pour-on fluralaner on Rhipicephalus microplus infestation in cattle and in pastures in a tropical climate region where up to five generations of this tick species can occur per year. Methods Forty-five naturally infested cattle were divided into three experimental groups: T01, treated with fluralaner (2.5 mg/kg) pour-on every 42 days; T02, the cattle received the first treatment with fluralaner on Day 0 but the next treatment involved a weekly visual evaluation; T03, control, received palliative treatment with a spray formulation when the group mean was ≥ 30 ticks. Counts of female R. microplus were performed weekly until day 343, and larval counts on pasture were performed on Days 0, 30, and 60 and every 30 days until Day 330. Results Using fluralaner, six applications were performed in Group T01, and four were performed in Group T02. In the control group (T03), it was necessary to perform eight palliative acaricide treatments with the spray formulation. The animals in T01 and T02 showed lower mean tick counts (p ≤ 0.05) than the control group (T03) on 28 and 27 of the 49 evaluated dates, respectively. In the paddock where the animals were kept as controls, the R. microplus larvae counts increased to 1458. In the paddocks where the animals were treated with fluralaner, the number was ≤ 19 per paddock during the study. Conclusions The different strategic treatment protocols performed with pour-on fluralaner (2.5 mg/kg) over a year in taurine cattle in a tropical region with a history of up to five annual generations of cattle ticks were effective, maintaining levels of R. microplus infestations in animals and in pastures close to zero in most of the study. Depending on the retreatment criterion adopted, the number of applications per year may be lower, resulting in a reduction in the mean cost of acaricide treatment per year and lower exposure of R. microplus populations to the active ingredient, resulting in lower resistance and selection pressure. Graphical Abstract